Pengaruh CR, DER, TATO, dan ROA Terhadap PBV Pada PT Indomobil Sukses Internasional Tbk - Kaniasari Wulan Dewi; Erna Herlinawati; Andre Suryaningprang; Yoyo Sudaryo (Journal Of Business, Finance, and Economics (JBFE), 2022)
Firm value is significant since it is thought to impact investors' perceptions of the firm. The purpose of this research is to examine the impact of the Current Ratio (CR), Debt to Equality Ratio (DER), Total Asset Turnover (TATO), and Return on Assets on the Price to Book Value (PBV) at PT Indomobil Sukses Internasional Tbk from 2012 to 2021. The quantitative research technique was applied, using a descriptive and verification approach. Purposive sampling is used in this approach. Following the application of the classical assumptions, multiple regression analysis, coefficient of determination analysis, and hypothesis testing were performed. The findings revealed that CR, TATO, and ROA had a substantial beneficial influence on PBV, but DER had a negative effect on PBV. Simultaneous test results demonstrate that CR, DER, TATO, and ROA have a considerable impact on PBV, accounting for 94.1% of the total, with the remaining 5.9% affected by other variables.